Rotary fatigue testing to determine the fatigue life of NiTi alloy wires: an experimental and numerical analisys - Carvalho, André (2020)
Endodontic rotary file instruments used to treat root canals in dentistry suffered breakthrough transformations in recent years when stainless steel was replaced by Nickel-Titanium (NiTi). NiTi alloys used in Endodontics possess superelastic properties at body temperature (37C) that bring many advantages on the overall performance of the root-canal treatment. They can follow curved root canals more easily than stainless steel instruments and have been reported to be more effective in the removal of the inflamed pulp tissue and protection of the tooth structure. However, these instruments eventually fracture under cyclic bending loading due to fatigue, without any visible signals of degradation to the practitioner. This problem brought new challenges on how new instruments should be tested, as NiTi alloys are highly non-linear and present a large hysteresis cycle in the Elastic domain. Current existing standards are only available for Stainless Steel testing. Thus, many authors have attempted to design systems that can test NiTi endodontic files under fatigue loads. However, no approach has been universally adopted by the community yet, as in most cases they are based on empirical set ups. Following a more systematic approach, this work presents the results of rotary fatigue tests for several NiTi wires from different manufacturers (Memry™ and Euroflex™). The formulation is presented, where the material strength reduction can be quantified from the determination of the strain and the number of cycles until failure, as well numerical FEM simulation to verify the analytical model predictions.